Improved wound management at lower cost: a sensible goal for Australia. Issue 3 (3rd December 2015) - Norman, Rosana E; Gibb, Michelle; Dyer, Anthony; Prentice, Jennifer; Yelland, Stephen; Cheng, Qinglu; Lazzarini, Peter A; Carville, Keryln; Innes‐Walker, Karen; Finlayson, Kathleen; Edwards, Helen; Burn, Edward; et al.
Abstract: Chronic wounds cost the Australian health system at least US$2·85 billion per year. Wound care services in Australia involve a complex mix of treatment options, health care sectors and funding mechanisms. It is clear that implementation of evidence‐based wound care coincides with large health improvements and cost savings, yet the majority of Australians with chronic wounds do not receive evidence‐based treatment. High initial treatment costs, inadequate reimbursement, poor financial incentives to invest in optimal care and limitations in clinical skills are major barriers to the adoption of evidence‐based wound care. Enhanced education and appropriate financial incentives in primary care will improve uptake of evidence‐based practice. Secondary‐level wound specialty clinics to fill referral gaps in the community, boosted by appropriate credentialing, will improve access to specialist care. In order to secure funding for better services in a competitive environment, evidence of cost‐effectiveness is required. Future effort to generate evidence on the cost‐effectiveness of wound management interventions should provide evidence that decision makers find easy to interpret. If this happens, and it will require a large effort of health services research, it could be used to inform future policy and decision‐making activities, reduce health care costs and improve patient outcomes.